PREGNANCY IN THE ADOLESCENCE IN THE MUNICIPAL DISTRICT OF SANTANA OF ACARAÚ-CEARÁ-BRAZIL: AN ANALYSIS OF THE CAUSES AND RISKS - Francisco Rosemiro Guimarães Ximenes Neto; Gerardo Magela Ponte Júnior (Universidade Federal de Goias, 2004)
The woman's reproductive function exposes her/it the tension and risk, during great part of your life.From the first indications of the puberty, when still child, the girls begin to wake up for the sexuality and, a lot oftimes, without orientation on the part of the family or of the educators. Sometimes beginning prematurely in thesexual life, some become mother children, in way conscious or unconscious. Inside of this context, the objectivesof the study were: To identify the possible causes that took the adolescents to become pregnant; To identify thepregnant adolescent's perception on the pregnancy and, to Characterize the adolescent pregnant women socialand economical and obstetric profile. The study is of the exploratory-descriptive type. The collection of data feltthrough a form, that was filled out by the Male nurses of Health of the Family of the municipal district of Santana ofAcaraú, in the period of May to June of 2003. The sample understands 33 pregnant adolescents attended by thestrategy. With the research he/she identified that: 80% of the adolescents have 15 to 19 years, 79% are single,73% of the adolescents are alphabetized, 76% of the adolescents don't have any professional activity. It is alsoobserved that 82% win less than a minimum wage, 61% of the adolescents had the first sexual relationship untilthe 15 years of age. In agreement with the data 88% they were in the first pregnancy and 67% don't make use ofany contraception type. The pregnancy in the adolescence is a problem of public health of social character, thatneeds the execution of healthy public politics for your reduction and improvement of the quality of the adolescents'life.